Differential and Prognostic Significance of HOXB7 in Gliomas - Zhou, Xingang; Liang, Tingyu; Deng, Jinhai; Ng, Kenrick; Li, Man; Lv, Chunxin; Chen, Jiamin; Yang, Kun; Ma, Zhiyuan; Ma, Wenping; Wang, Peng (Frontiers in Cell and Developmental Biology, 2021)
Diffuse glioma is the most common primary tumor of the central nervous system. The prognosis of the individual tumor is heavily dependent on its grade and subtype. Homeobox B7 (HOXB7), a member of the homeobox family, is abnormally overexpressed in a variety of tumors. However, its function in glioma is unclear. In this study, HOXB7 mRNA and protein expression levels were analyzed in 401 gliomas from the CGGA RNA-seq database (325 cases) and our hospital (76 cases). HOXB7 expression, at both mRNA and protein levels, were upregulated in glioblastoma (GBM) and Isocitrate dehydrogenase 1(IDH1) wild-type glioma tissues. Kaplan-Meier with log-rank test showed that patients with high HOXB7 expression had a poor prognosis (p< 0.0001). Moreover, HOXB7 protein was deleted in 90.9% (20/22) of oligodendrogliomas and 13.0% (3/23) of astrocytomas. The sensitivity and specificity of HOXB7 protein deletion in oligodendroglioma were 90.9% (20/22) and 87.0% (20/23), respectively. To verify the reliability of using HOXB7 in differentiating oligodendroglioma, we used 1p/19q Fluorescence In Situ Hybridization（FISH) testing as a positive control. The Cohen's kappa coefficient of HOXB7 immunohistochemistry staining and 1p/19q FISH testing was 0.778 (95% CI: 0.594-0.962, p< 0.001). In conclusion, HOXB7 is an independent predictor of poor prognosis in all grade gliomas. Additionally, HOXB7 is also a highly sensitive and specific indicator to differentiate oligodendroglioma from astrocytoma.